Penerapan Sistem Akuntansi Penggajian Dalam Kaitannya Dengan Sistem Manajemen Mutu (ISO 9001:2008) - Iriyadi, Iriyadi; Edison, Edison; Nurdini, Saras Ayu Adistya (Institut Bisnis dan Informatika Kesatuan, 2015)
An accounting system is necessary to ensure the company running consistently and efficiently to produce a good performance. One way that can be applied to achieve the goal or objective is to be a synergy with the accounting system of quality management systems (ISO 9001: 2008) which is usually referred to by the Intemational Standard Organization (ISO). Standards become mandatory for many manufacturers or companies to be able to compete in the intemational market, by demonstrating the consistency of the product quality. The purposes of this paper, are to recognize the payroll accounting system implementation at PT. Rahayu Santosa, and identifiy the implementation of quality management system (ISO 9001: 2008) at PT. Rahayu Santosa.The result show that the application of payroll accounting system does not have a direct relation with the quality management system (ISO 9001: 2008), but the quality management system (ISO 9001: 2008) ensures the procedure of a good payroll system. Keywords : ISO 9001:2008 and Accounting System